“I could still see her in my mind’s eye”: Water and Maternal Imagery in Uwe Johnson’s Anniversaries: From the Life of Gesine Cresspahl - Caroline Rupprecht (Studies in 20th & 21st Century Literature, 2010)
This article analyzes the writings of East German author Uwe Johnson (1934-84) in terms of his experimental style—specifically transitions between descriptive passages—in conjunction with maternal imagery, as discussed through reference to Susan Suleiman’s concept of a “1.5 generation” of Holocaust survivors. A non-Jewish German author, Johnson addresses German history from the position of the perpetrators, yet born in 1934, he experienced National Socialism from the point of view of a child. In his tetralogy, Anniversaries: From the Life of Gesine Cresspahl (1970-83), feelings of guilt and attempts to understand the German past are negotiated through the maternal figure. This figure is linked, in turn, to water as both a structural and symbolic element throughout the novel. As this article demonstrates, the effect of “blurred boundaries” is achieved through water, which functions as paradigm for the mother-daughter relationship: the narrator-protagonist Gesine’s memory is shaped by the experience of near-drowning before the eyes of her mother, Lisbeth, who commits suicide via self-immolation during Reichskristallnacht. As this article concludes, the author himself seems caught in the predicament of Suleiman’s 1.5 Generation, where perception is blurred, and immersing oneself in (imaginary) bodies of water becomes a response to the madness of fascism.
Keywords: East German; Uwe Johnson; maternal imagery; Susan Suleiman; 1.5 Generation; Holocaust survivors; National Socialism; Anniversaries: From the Life of Gesine Cresspahl; maternal figure; mother; mother figure; vergangenheitsbewältigung; blurred boundaries; water; water imagery; mother-daughter relationship; fascism